The Influence Of Price Perception, Store Ratings, And Flash Sales On Purchase Decisions In Marketplaces - Cinta Kusuma Dewi; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research focuses on the factors influencing purchase decisions in marketplaces, specifically price perception, store ratings, and flash sales. The study population consists of active students from the University of 17 August 1945 Surabaya, with a sample of 96 respondents selected using the Lemeshow formula. The analysis method applied is multiple linear regression using SPSS 25, employing a descriptive quantitative approach. The t-test results show that price perception, store ratings, and flash sales have a positive and significant effect on purchase decisions in marketplaces. The F-test indicates that, simultaneously, these three factors also have a positive and significant effect on purchase decisions. This research contributes to understanding the factors influencing purchase decisions in marketplace environments, particularly among active students.